2019
DOI: 10.1093/inthealth/ihz077
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision making in musculoskeletal pain consultations in low- and middle-income countries: a systematic review

Abstract: Background Global populations, especially those in low- and middle-income countries (LMICs), are at an increased risk of musculoskeletal (MSK) pain, a leading cause of years lived with disability. Shared decision making (SDM) in the management of these conditions may drive improvements in healthcare outcomes and quality. This study aimed to synthesize and appraise available evidence regarding SDM in MSK pain consultations in LMICs. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…This complements findings from other developing countries that have reported low patients' participation in decision making during their treatment. [21][22][23] In Uganda, a study among breast cancer patients showed that 80% of them were not given a chance to participate in the selection of their treatment options. 11 However, higher participation in SDM has been reported in some developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…This complements findings from other developing countries that have reported low patients' participation in decision making during their treatment. [21][22][23] In Uganda, a study among breast cancer patients showed that 80% of them were not given a chance to participate in the selection of their treatment options. 11 However, higher participation in SDM has been reported in some developed countries.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients from lowand middle-income countries are less likely to engage in SDM for reasons that may include limited awareness of their medical condition and differing cultural beliefs. 24 However, a recent meta-analysis found that SDM is more beneficial for patients with low health literacy compared to patients with high health literacy. 25 Future intervention studies engaging women with a GDM history in SDM for type 2 diabetes prevention should include women across the spectrum of educational attainment and should not exclude women with low health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…É uma condição multifatorial pois envolve interações complexas entre estruturas físicas, psicológicas, sociais, de estilo de vida e comorbilidades (Caneiro, Bunzli, & O'Sullivan, 2021). Requerem uma gestão a longo prazo e aumentam a pressão sobre os serviços de saúde (Sam, Sharma, Corp, Igwesi-Chidobe, & Babatunde, 2020). Para tentar compreender a resposta comportamental de um paciente à dor ME devemos avaliar (Quadro 4).…”
Section: A Resposta Comportamental Do Paciente Aos Seus Sintomasunclassified